Developing Educational Foundations to Develop Technological Awareness for Public Jordanian University Students Facing Information Revolution Challenges - Wedad Ali Aljamal; "Mohammad Ameen" Hamed Al-Quda (University of Science and Technology, Yemen, 2017)
This study aimed at developing educational foundations to develop technological awareness for the students of public Jordanian Universities  who face   challenges of information revolution. The study sample consisted of (342) faculty members of the public Jordanian universities in first semester of the academic year (2014/2015). To achieve the objectives of this study the developmental, analytical survey method was used.  Based on reviewing relevant literature and previous studies a set of educational foundations related to technological awareness was proposed.           The study results showed  that the degree of faculty members' approval of the proposed for the development of technological awareness among students of educational foundations was high. The findings have also shown statistically significant differences that were attributed to the experience variable, in favor of those of less than 3 years of experience, and to the variable of academic rank in the area of accreditation and scientific research in favour of full time lecturers.           Based on Factor Analysis of statements pertaining to the results have revealed saturation of the first factor for  the 42 statements which make up the whole research tool. Thus, these 42 statements constitute the proposed educational foundations to develop technological awareness among the students of public Jordanian University in order to be able to face the challenges of Information Revolution. The researchers recommended the adoption of these foundations by public Jordanian universities.